Living on the move: The city understood from public space and urban mobility - Evans Morales, Franco (2020)
The article starts by understanding the city as an element of urban life through public space and urban mobility. For this, a reflection is made on what has been produced about public space from the urban planning perspective, considering the legal, citizenship, and conflict approaches as well as its dimensions in the physical-territorial, economic, political, and cultural aspects. On the other hand, urban mobility is addressed as a social practice of traveling that combines the demands and the capabilities to satisfy them, differentiating it from the transport system. It is concluded that the public space as an analytical category is in constant tension since it shares both integration and conflict logics, and sheds a dim light over new ways of conceiving the concepts of public and private. Whereas urban mobility is not only a technical means of displacement like transportation, but prioritizes the mobility needs of people, their travel experiences, conditions in which it takes place, as well as perceived advantages and difficulties.